95.16-Gb/s Mode-Division-Multiplexing Signal Transmission in Free-Space Enabled by Effective-Conversion of Vector Beams - Jianbo Zhang; Fan Li; Jianping Li; Zhaohui Li (IEEE Photonics Journal)
We introduce a high-efficient vector modes (VMs) conversion scheme by using Q-plate (QP) and half-waveplate based on higher-order Poincaré sphere model. Enabled by this simple mode conversion scheme, we demonstrate a 95.16-Gb/s vector-mode-division-multiplexing (VMDM) transmission with direct-detection orthogonal-frequency-division-multiplexing signal over ∼20-cm free space optical link. The mode crosstalk of four typical cylindrical VMs (TE01, TM01, HE21e, and HE21o) are less than −10.3 dB and can be further optimized by high-quality QP. The experimental results indicate that the VMDM technique can be a powerful candidate for large-capacity short-reach optical interconnects.